Compact Multiband Interdigital-Coupled-Fed Planar Antenna with Stepped-Impedance Structures for Mobile Handsets - Tao Zhou; Yazi Cao; Zhiqun Cheng (International Journal of Antennas and Propagation)
A new compact multiband planar antenna combining an interdigital-coupled feeding line and one stepped-impedance structure is presented here. This antenna is capable of generating five resonant modes to cover the ISM 915/2400/5800 MHz bands, GPS band, and IMT C-band, respectively. The five resonant frequencies covered by the proposed antenna can be adjusted individually by controlling the impedances and electrical lengths of the corresponding stepped-impedance sections. An additional advantage of the proposed stepped-impedance structure is its ability to suppress higher order resonance modes, thus filtering out unwanted interference. The proposed antenna utilizes a simple planar compact structure and occupies a small area of only 12 × 30 mm2. Details of the antenna design and experimental results are presented and discussed.